Clinical characteristics and prognostic factors of patients with cyanotic congenital cardiopathies that are taken to pulmonary system pulmonary of central type or modified Blalock Taussig, between January 2006 and June 2017: Retrospective multivariate... - Rios Giovanny; Molina German; Correa Juan; Díaz Carlos; Rojas Johanna (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2019)
Overall objective: Identify the more important variables that determine the prognosis and survival of patients with cyanotic heart disease who that underwent to pulmonary systemic fi stula in San Ignacio Hospital between January 2006 and June 2017. Methods: The database of the Cardiovascular Surgery service of the San Ignacio Hospital was reviewed from January 2006 to June 2017. From this registry, the information of the identity documents of the patients to be included in the study was obtained, in order to obtain the data of the variables to be studied from the electronic medical record of the San Ignacio Hospital.